Formulasi Dan Uji Stabilitas Sediaan Toner Anti Jerawat Ekstrak Bunga Melati (Jasminum sambac L.) - Karami, Muhammad Rian Al Nafis; Malahayati, Siti; Hidayah, Nurul; Budi, Setia (Jurnal Farmasi SYIFA, 2023)
Toners can prevent residue and sebum from absorbing into facial pores which can cause various kinds of skin problems such as acne. Jasmine flowers contain ingredients that can inhibit Staphylococcus epidermidis bacteria and Shigella flexneri bacteria at a concentration of 10%, which are bacteria that cause acne. Objective to analyzing the effect of varying concentrations of surfactants on the stability of anti-acne toner preparations of jasmine flower extract and identifying the optimal formulation based on the evaluation results of anti-acne toner preparations of jasmine flower extract. Methods the laboratory experiment used a quasy-experimental method without a control group with a one-group posttest only design. Jasmine flower extract was formulated in 2 formulas with variations in polysorbate 20 concentration of 5% and 5.65%, then a stability test was carried out using the cycling test method for 12 days for 6 cycles by evaluating before and after stability testing, including organoleptic, homogeneity, viscosity, and pH. The results showed that toner preparations of jasmine flower extract (Jasminum sambac L) with various surfactant concentrations showed differences in organoleptic, homogeneity, pH, and viscosity. The pH test is not stable (p 0,000). Test viscosity formula I (p 0.081) stable, formula II (p 0.400). Conclusion from the two formulas in the manufacture of toner preparations of jasmine flower extract with variations in surfactant concentration from the results of all cycles in the cycling test, the evaluation results were physically stable but chemically unstable so that there was no optimal formula.